Answer:
[tex]x=\dfrac{-(-15)\pm\sqrt{(-15)^2-4(-2)(-3)} }{2(-2)}[/tex]
Step-by-step explanation:
Given equation: [tex]-2x^2 - 11x + 7 = 10 + 4x[/tex]
First, rearrange the equation so that it is in the general form of [tex]ax^2+bx+c=0[/tex]
[tex]-2x^2 - 11x + 7 = 10 + 4x[/tex]
Subtract 4x from both sides:
[tex]-2x^2 - 15x + 7 = 10[/tex]
Subtract 10 from both sides:
[tex]-2x^2 - 15x - 3 = 0[/tex]
Therefore,
- [tex]a=-2[/tex]
- [tex]b=-15[/tex]
- [tex]c=-3[/tex]
Input these values into the quadratic formula:
[tex]x=\dfrac{-b\pm\sqrt{b^2-4ac} }{2a}[/tex]
Therefore,
[tex]x=\dfrac{-(-15)\pm\sqrt{(-15)^2-4(-2)(-3)} }{2(-2)}[/tex]